System dynamics analysis of the paddy deduction system in the MADA granary area in Malaysia - Rusli, Rawaida (2018)
Paddy deduction rate refers to the ratio of bad paddy to the total paddy produce sold to the buyers including millers and other intermediaries. It is important to ensure good quality of paddy before processing it to rice. However, the determination of paddy deduction rate often goes above the deduction rate recommended by the government. Therefore, this study examines the decision making process in deriving the paddy deduction rate that mutually agreed both by the farmers and millers in the MADA area which is the largest granary area in the country. A system dynamics methodology is used to capture the complexity of decision making of the major actors at the farm level market. The complexity characteristics include: feedback relationship or circular causality between decisions made by sellers and buyers, delays and non-linearity behavior. A system dynamics model representing such decision making was developed and assessed by simulating three different scenarios. They are: (i) maximizing good farm practices, (ii) increasing the capacity of combine harvester and (iii) adjustment by the government on the domestic paddy price and retail prices. Their impacts on deduction rate, moisture content, farmers’ income and millers’ profitability were subsequently investigated. This study revealed that maximizing farm practices, increasing the capacity of combine harvester machine, adjustment by the government in the domestic paddy price and retail price have significant impacts on the determination of the desired paddy deduction rate between the farmers and millers in the MADA granary area. The simulation results suggested that the Scenario Three (S3), which comprised the changes in the farm practices, machine harvester efficiency, domestic paddy price and retail price rice, produced the most significant impacts on the paddy deduction rate imposed on the farmers and changes in the miller’s profitability. Therefore this study suggests that there is a need for the farmers to maximize their farm practices in order to achieve the lower paddy deduction rate.The better farm practices adopted by the farmers, the lower the paddy deduction will be.